The Influence of the Unemployment Rate, Population Size, and Wages on Economic Growth during the Administration of President Joko Widodo - Almagribi, Ahmad Bilal; Redjeki, Sri (Jurnal EMT KITA, 2026)
Economic growth is one indicator of a government's success. President Joko Widodo's two terms have received positive responses from several researchers. Unfortunately, no research has focused on examining economic growth during these two periods. This article aims to examine the influence of the unemployment rate, population, and wages on Indonesia's economic growth during President Joko Widodo's administration. This study uses a quantitative approach with secondary data sources obtained from the Central Statistics Agency (BPS) report for 34 provinces in Indonesia for the period 2016-2024. Data analysis uses the Multiple Regression method for Panel Data with Eviews 12 software. The results of the study indicate that the unemployment rate does not significantly influence economic growth, with a probability value of 0.344 > 0.05. Meanwhile, population and wages significantly influence economic growth, with probability values of 0.000 < 0.05 and 0.000 < 0.05, respectively. Although based on this study, the unemployment rate does not negatively affect economic growth, the government still needs to continue to strive to reduce the unemployment rate to achieve public welfare.
Keywords: Unemployment; Population; Wages; Economic Growth; Indonesia; President Joko Widodo